Togo : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This Selected Issues paper provides an assessment of the redistributive impact of fiscal policies in Togo by estimating the impact of taxation and spending on household-level income inequality and poverty rates. Although the combination of direct taxes and subsidies is found to reduce inequality, it increases poverty rates, as the value of taxes paid by lower-income households outweighs the value of transfers they receive, increasing the share of the population living below the poverty line. These findings highlight the importance of targeting spending to lower-income households as the authorities progressively shift public spending from infrastructure to social expenditures.